The Dramaturgy of Religious Tolerance: Representing Religious Group Identities in the Public Sphere of Contemporary Urban Society - Hamdan Hamdani; Theguh Saumantri (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
This study explores the representation of religious identity in the public sphere to express religious beliefs and strengthen social cohesion through interfaith interactions. Drawing on Erving Goffman’s dramaturgical theory, this study examines how religious identity is performed to foster social harmony. Using a descriptive qualitative and phenomenological design, the research was based on observations, in-depth interviews with religious and community leaders, and document analysis. The findings indicate that religious groups use the front stage to promote tolerance through interfaith rituals, community service, and symbols of peace. At the same time, the backstage enables religious leaders as mediators of tolerance. These performances are shaped by social scripts grounded in tolerance narratives and local cultural values. Impression management strategies include inclusive language, interfaith symbols, and adaptive behavior to create a positive public image. Audience responses vary, reflecting appreciation for harmony-building efforts and criticism of representations viewed as symbolic or insufficiently inclusive. Keywords: Dramaturgy; Religious Tolerance; Urban Society; Public Sphere